IMPACT OF THE EXISTENCE OF THE MANDALIKA CIRCUIT ON THE COMMUNITY ECONOMY IN KUTA VILLAGE, CENTRAL LOMBOK - Iswandi, L. Muhamad (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2024)
This research is motivated by the existence of the Mandalika Circuit which has brought changes to the people of Kuta Village, Pujut District, Central Lombok Regency. This research uses a descriptive-analytic research method that analyzes the data found with data obtained in the field. The method used to obtain data is by using observation, interviews and documentation methods. As well as data analysis using the data reduction stage, data presentation or data display stage and verification or conclusion drawing stage. The results of this research show that the impact of the existence of the Mandalika Circuit on the income of the people of Kuta Village, Pujut District, Central Lombok Regency has had a positive impact on the economy of the people of Kuta Village. Especially for business actors in Kuta Village, they really feel the change in their business income compared to their income before the Mandalika Circuit existed.